The issues and challenges of local government units in the era of population ageing - Katarzyna Maj-Waśniowska; Tomasz Jedynak (Administrative Sciences, 2020)
So far, issues related to the effects of ageing have been studied mainly from the perspective of national policy and international analyses. The study fills the research gap in this area focusing on the impact of demographic changes on the policy of local government units (LGUs). In the first section, a literature review of the research conducted so far has been performed. The empirical part contains the results of the study that was carried out on a sample of 131 municipalities of the Ma±opolska Voivodeship. The results obtained were subject to statistical analysis, based upon elements of descriptive statistics, cluster analysis and hierarchical clustering (k-means algorithm, Ward's method) and statistical inference (Chi-square tests). It was found that the most important social problems identified by municipalities include in particular: demographic processes (indicated as significant by 71% of municipalities), population migrations (76%), unemployment (88%), alcoholism (93%) and poverty (75%). On the other hand, the following problems are perceived to a lesser extent: deficits in the level of education (15%) and social capital (36%), as well as participation in public (31%) and cultural (34%) life. However, only a few municipalities, mainly ones that are larger and more urbanised, see the key importance of the intensity of the ageing process (33% of cities with powiat rights, 14% of urban municipalities and only 4% of rural municipalities). Studies also indicate that in the light of the diagnosis of current problems, the greatest challenges associated with an ageing population are related to the lack of adequate financial resources, a decrease in a municipality's income, a deteriorating situation in the local labour market, reduced family care potential, increased health care costs and social aid. It was also noted that from the municipalities' point of view, the consequences of an ageing population will not only have a financial dimension, but will also require a certain redefinition of the catalogue of tasks to be carried out.
Keywords: 350; ageing of society; demographic changes; local government units; public tasks; social problems